A pregnant woman died of sudden cardiac death: Should esophageal foreign body be considered an inductive factor? A case report and literature review - Chang Cao; Mingming Li; Zhanzhan Liu; Shiyong Fang; Gang Chen; Guang Chen; Tongjun Ma; Xuyang Zhu; Xiang Xu (Wolters Kluwer Medknow Publications, 2022)
Here, we report a case of acute attack of coronary heart disease (CHD). A 47-year-old pregnant woman with gestational hypertension developed sudden-onset chest tightness, palpitations, dyspnea, and cyanosis of the face and lips after admission. Her blood pressure was 180/110 mmHg and her blood oxygen saturation was 45% at that time. After cardiopulmonary resuscitation, a weak heartbeat was restored, but oxygen saturation did not increase significantly. Therefore, she was transferred to the intensive care unit; however, she died after 21 days of admission. Autopsy findings revealed that a foreign body was embedded in the esophagus near the right piriform, and her heart weighed 392 g; histopathological examination revealed CHD, thrombosis in the lumen of the right coronary artery, cardiomyocyte hypertrophy, vascular hyaline degeneration in arterioles, neutrophils in the bronchiole and alveolar. All the tested samples yielded negative toxicological results. Clinical status and autopsy findings were not compatible with a diagnosis of peripartum cardiomyopathy. The patient's sudden death was attributed to CHD, and esophageal foreign-body impaction was considered to be concomitant phenomenon. Our findings might help in increasing the awareness between esophageal foreign-body impaction and sudden cardiac death and they can also help in clarifying that understanding the primary cause of death is the key to resolving an iatrogenic medical tangle.